Lithium-ion battery explosion aerosols: Morphology and elemental composition. Issue 10 (3rd October 2021) - Barone, Teresa L.; Dubaniewicz, Thomas H.; Friend, Sherri A.; Zlochower, Isaac A.; Bugarski, Aleksandar D.; Rayyan, Naseem S.
Abstract: Aerosols emitted by the explosion of lithium-ion batteries were characterized to assess potential exposures. The explosions were initiated by activating thermal runaway in three commercial batteries: (1) lithium nickel manganese cobalt oxide (NMC), (2) lithium iron phosphate (LFP), and (3) lithium titanate oxide (LTO). Post-explosion aerosols were collected on anodisc filters and analyzed by scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy (EDS). The SEM and EDS analyses showed that aerosol morphologies and compositions were comparable to individual grains within the original battery materials for the NMC cell, which points to the fracture and ejection of the original battery components during the explosion. In contrast, the LFP cell emitted carbonaceous cenospheres, which suggests aerosol formation by the decomposition of organics within molten microspheres. LTO explosion aerosols showed characteristics of both types of emissions. The abundance of elements from the anode, cathode, and separator in respirable aerosols underscored the need for the selection of low-toxicity battery materials due to potential exposures in the event of battery thermal runaway.